Pediatric, adult, and late onset multiple sclerosis: Cognitive phenotypes and gray matter atrophy - Ermelinda De Meo; Emilio Portaccio; Rosa Cortese; Luis Ruano; Benedetta Goretti; Claudia Niccolai; Francesco Patti; Clara Chisari; Paolo Gallo; Paola Grossi; Angelo Ghezzi; Marco Roscio; et al. (Annals of Clinical and Translational Neurology)
Abstract Objectives We aim to investigate cognitive phenotype distribution and MRI correlates across pediatric‐, elderly‐, and adult‐onset MS patients as a function of disease duration. Methods In this cross‐sectional study, we enrolled 1262 MS patients and 238 healthy controls, with neurological and cognitive assessments. A subset of 222 MS patients and 92 controls underwent 3T‐MRI scan for brain atrophy and lesion analysis. Multinomial probabilistic models identified likelihood of belonging to cognitive phenotypes (“preserved‐cognition,” “mild verbal memory/semantic fluency,” “mild multi‐domain,” “severe attention/executive,” and “severe multi‐domain”) and experiencing MRI abnormalities based on disease duration and age at onset. Results In all groups, the likelihood of “preserved‐cognition” phenotype decreased, whereas “mild multi‐domain” increased with longer disease duration. In pediatric‐ and adult‐onset patients, the likelihood of “mild verbal memory/semantic fluency” phenotypes decreased with longer disease duration, and that of “severe multi‐domain” increased with longer disease duration. Only in adult‐onset patients, the likelihood of “severe executive/attention” phenotype increased with longer disease duration. All groups displayed escalating probabilities of cortical, thalamic, hippocampal, and deep gray matter atrophy over disease course. Compared to adult, pediatric‐onset patients showed lower probability of experiencing thalamic atrophy with longer disease duration, while elderly‐onset showed higher probability of experiencing cortical and hippocampal atrophy. Interpretation Age at MS onset significantly influences the distribution of cognitive phenotypes and the patterns of regional gray matter atrophy throughout the disease course.